Increased risk of bladder cancer in young adult men with hyperlipidemia: A population-based cohort study. Issue 48 (3rd December 2021) - Shih, Hung-Jen; Lin, Ke-Hsun; Wen, Yu-Ching; Fan, Yen-Chun; Tsai, Pei-Shan; Huang, Chun-Jen
Abstract : Abstract: A high-cholesterol diet increases the risk of bladder cancer. The purpose of this nationwide longitudinal population-based retrospective cohort study is to investigate whether hyperlipidemia is a risk factor for bladder cancer. Data from Taiwan National Health Insurance Database were analyzed. The primary study end point was the occurrence of newly diagnosed bladder cancer. The relative risk of bladder cancer in a hyperlipidemia cohort was compared with that in an age- and gender-matched non-hyperlipidemia cohort by using the Cox proportional hazards regression model. Cox regression analyses were further adjusted by the propensity score. Our data revealed that the hyperlipidemia cohort (n = 33, 555) had a significantly higher subsequent risk of bladder cancer than did the non-hyperlipidemia cohort (n = 33, 555) (adjusted hazard ratio [HR] = 1.37, P = .005) after propensity score adjustment. Subgroup analyses revealed that men in the hyperlipidemia cohort had a significantly higher subsequent risk of bladder cancer than did those in the non-hyperlipidemia cohort (adjusted HR = 1.36, P = .040). However, the risk of bladder cancer was not significantly different between women in the hyperlipidemia cohort and those in the non-hyperlipidemia cohort. Subgroup analyses further revealed that the risk of bladder cancer was significantly higher in men aged 20 to 39 years in the hyperlipidemia cohort than in those in the non-hyperlipidemia cohort (adjusted HR = 5.45, P = .029). In conclusion, hyperlipidemia is a risk factor for bladder cancer in young adult men.